ESTIMASI CADANGAN KARBON PADA TANAH BEKAS TAMBANG EMAS DI KABUPATEN DHARMASRAYA, SUMATERA BARAT - Amsar Maulana; Mimien Harianti; Teguh Budi Prasetyo; Herviyanti Herviyanti (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Climate change, deforestation, and substantial loss of agricultural land within gold mining concessions in Dharmasraya greatly affect soil carbon stocks (Cs). This study used a survey method with purposive random sampling based on variations in ex-gold mining areas in each region, at depths of 0-20 and 20-40 cm with three to five replicates with a total of 54 samples. The estimation of Cs in ex-gold mining soil was highest at a depth of 20-40 cm (5.89E2), compared to a depth of 0-20 cm (1.38E2), where bulk density (BD), soil organic carbon (SOC), and total Hg in ex-gold mining soil at a depth of 0-20 and 20-40 cm were 1.46 and 1.39 g cm-3; 0.03 and 0.05%; 4.11 and 4.25 mg kg-1, respectively. The Cs in ex-gold mining soil at a depth of 0-20 cm is very significant by BD (r=-0.522** or Cs=-628.03(BD)+1055.1; R²=0.275) and SOC (r=0.948** or Cs=4896.8(SOC)-6.4673; R²=0.8996) and total Hg (r=0.518** or Cs=81.373(Hg)-196.43; R²=0.2688). However, at a depth of 20-40 cm, it was very significant by SOC (r=0.836** or Cs=16666(SOC)-196.03; R²=0.699).